3.18 A novel SSVEP device for neurological assessment following concussion - Mahony, Dylan; Tyler, Hoang; Anton, Nathanson; Natasha, Tanudji; Adrian, Cohen (British journal of sports medicine, 2024)
ObjectiveThe aim of this study was to investigate the use of a novel SSVEP device as a neurophysiological marker of concussion. This study’s research question was to assess the level of agreement between the device and a doctor’s diagnosis of concussion.Outcome MeasuresOver 1,000 participants have been measured for this study, including 68 concussion measurements. The average age of the participants was 25 with a male:female ratio of 4:1. Subjects were excluded if they had a history of epilepsy, seizures, sensitivity to flashing lights or legal blindness. This study has been approved by the Bellberry HREC Committee (HREC #2018–10–891).Participants were recruited from over 20 sites in Australia, including athletes from Rugby Union, Rugby League, and Australian Rules Football. After a head impact, a doctor assessed the player and made a diagnosis of concussion or not. In both situations, participants were also measured using the device and separated into the ‘confirmed concussion’ or ‘no concussion’ group. SSVEP measurement was randomly assigned before or after the doctor’s diagnosis.Main ResultsA machine learning (ML) algorithm was used to classify the SSVEP data as being a concussion or not. The level of agreement between the ML algorithm and doctors’ diagnosis was quantified. Preliminary cross-validation returned a sensitivity of 85%, with a specificity of 70%. These figures are in line with other devices used in neurological assessment.ConclusionsFurther refinement and validation of this protocol may lead to the production of a device which assists health care professionals make a more informed concussion assessment.